2016
DOI: 10.1080/00015458.2015.1136496
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of permanent vascular access for haemodialysis in patients with end-stage renal disease in Cameroon: results from the pilot experience of the Douala general hospital

Abstract: Background Chronic Kidney disease is a major health problem in the world. Native arteriovenous Fistula (AVF) is well established as the best vascular access for haemodialysis. Little is known about the outcome of AVF in sub-Saharan Africa. We aim to analyze the outcome of patients undergoing AVF creation during the pilot program established at the Douala general hospital (DGH). Method This was hospital-based, longitudinal study with a retrospective phase (April 2010-January 2014) and a prospective phase (Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The introduction of ultrasound guidance has improved peripheral nerve block as compared to electrical nerve stimulation (Ozturk et al, 2016;Abrahams et al, 2009). A study carried out at the Douala General Hospital (DGH) showed that out of 85 vascular accesses created only two-third were functional (done under either general anaesthesia or local anaesthesia) for haemodialysis sessions (Ngatchou et al, 2016). However, in 2017 ultrasound regional anaesthesia camein at the aforementioned health institution as the main anaesthetic modality for AVF creation.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of ultrasound guidance has improved peripheral nerve block as compared to electrical nerve stimulation (Ozturk et al, 2016;Abrahams et al, 2009). A study carried out at the Douala General Hospital (DGH) showed that out of 85 vascular accesses created only two-third were functional (done under either general anaesthesia or local anaesthesia) for haemodialysis sessions (Ngatchou et al, 2016). However, in 2017 ultrasound regional anaesthesia camein at the aforementioned health institution as the main anaesthetic modality for AVF creation.…”
Section: Introductionmentioning
confidence: 99%